Pengaruh Gaji, Insentif, dan Motivasi Kerja terhadap Kinerja Karyawan PT. Pan Pacific Jakarta Cabang Semarang - Intan Raysita; Putu Sulastri (Dharma Ekonomi, 2024)
This research aims to determine the effect of salary, incentives and motivation on the performance of PT employees. Pan Pacific Jakarta Semarang Branch. The data used is primary data, namely data obtained through questionnaires distributed to PT employees. Pan Pacific Jakarta Semarang Branch The sampling used in this research was simple random sampling. The number of samples in this research was 62 employees from 162 populations by using the Slovin formula. Then the data collection method is through questionnaires and data analysis using SPSS which includes validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, F test, as well as hypothesis testing using the t test and R2. The research results are 1). Salary (X1) has a positive effect on employee performance (Y). This is proven by the calculated t value of 2.384 > t calculated 2.000 with a significance value of 0.020 < 0.05 (significant). 2). Incentives (X2) have no effect on employee performance (Y). This is proven by the calculated t value of 1.453 < t table 2.000 with a significance value of 0.152 > 0.05 (not significant). 3). The influence of motivation (X3) has a positive effect on employee performance (Y). This is proven by the calculated t value of 2.545 > t table 2.000 with a significance value of 0.014 < 0.05 (significant).